Barbados : 2007 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the economy of Barbados has been growing at a solid pace, and the outlook for 2007 is generally favorable. Robust output growth of about 4 percent is expected to continue in 2007, supported by tourism and construction. Inflation, which was pushed up in 2006 by higher energy prices and a temporary import surcharge, is set to decelerate to 5 1\2 percent in 2007. However, the current account deficit, despite having narrowed in 2006, is still high and projected to remain unchanged at about 8 1\2 percent of GDP.